Aspects of trypanotolerance and associations with growth rate in post-weaner N'Dama cattle under high trypanosomiasis risk - Maille, J.C.; Authié, Edith; D'Ieteren, G.D.M.; Leak, S.G.A.; Maehl, J.H.H.; Nagda, S.M.; Rarieya, J.M.; Rowlands, G.J.; Sauveroche, B.; Thorpe, W.R.; Trail, J.C.M.; Yangari, G. (OAU/STRC, 1991)
A study conducted to find out the ability of N'Dama cattle to control parasitaemia and anaemia at a ranch in Gabon. Examines the effect of parasitaemia on daily liveweight change.